Immunological Protection of Individuals Aged 3 to 25 Years Against Pertussis: Regional Cross-Sectional Study - Diana V. Sutovskaya; Alla V. Burlutskaya; Larisa V. Dubova; Daria R. Krylova (Вопросы современной педиатрии, 2021)
Background. Recently, there has been an increase in the incidence of pertussis in unvaccinated, as well as vaccinated children and adults. The major risk group for pertussis are infants and children over 4 years of age due to gradual decrease in basic immunity. Objective. The aim of the study was to analyze postvaccinal immunity against pertussis in individuals aged 3 to 25 years in Krasnodar. Methods. The study was carried out in the period between July 2018 and October 2019 and included patients aged 3 to 25 years with completed (according to National Immunization Schedule) immunization against pertussis with no history of pertussis in the past. Postvaccinal immunity against pertussis in this sample was determined by the ratio of study participants with minimum protective antibodies titer to Bordetella pertussis (≥ 1:160). Results. The minimum protective antibody titer was revealed in 24 out of 76 participants. Distribution to age groups was the following: children aged 3 to 7 years — 2/28 (7%), 8 to 17 years — 13/22 (59%; p < 0.001, compared with the younger age group), ≥ 18 years — 9/26 (35%; p = 0.017). There was no postvaccinal immunity (no antibodies detected) in 6 (21%), 1 (5%) and 4 (15%) participants, respectively. Conclusion. Insufficient postvaccinal (humoral) immunity against pertussis was revealed in majority of children under 7 years. The ratio of such children decreases with age. It suggests the presence of hidden circulation of Bordetella pertussis and, as a result, previous medical condition in erased or abortive form.